Hubungan Dukungan Keluarga terhadap Gangguan Citra Tubuh pada Pasien Kemoterapi - Siti Fatimah; Wahyu Endang Setyowati; Dwi Heppy Rochmawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aimed to identify the relationship between family support and body image disturbance among breast cancer patients undergoing chemotherapy at Sultan Agung Islamic Hospital, Semarang. Breast cancer and its treatment, particularly chemotherapy, often cause physical changes such as hair loss, weight fluctuations, and mastectomy, which can significantly affect patients’ body image perception. Family support is assumed to play a crucial role in helping patients adapt to these changes. This research employed a quantitative approach with a cross-sectional design. A total of 110 breast cancer patients were recruited using consecutive sampling. The research instruments consisted of a family support questionnaire comprising 20 items and a body image questionnaire with 10 items. Data were analyzed using Spearman’s Rank correlation test with a significance level of 0.05. The results showed that most respondents (60%) received good family support, while 55% experienced negative body image. Statistical analysis revealed a significant relationship between family support and body image disturbance (p = 0.004) with a correlation coefficient of r = 0.275, indicating a weak but significant correlation. These findings suggest that family support plays an important role in maintaining a positive body image among breast cancer patients undergoing chemotherapy. Therefore, nursing interventions should actively involve family members to provide both emotional and practical support, which may help patients cope with the psychological impact of treatment and improve their overall well-being.